Pe Pengaruh Lingkungan Pondok Pesantren Terhadap Hasil Belajar Kimia Siswa Di MA NW Narmada - Unsalhusna, Ziadati; Lalu Rudyat Telly Savalas; Muti’ah (FKIP University of Mataram, 2024)
This research investigates the influence of the Islamic boarding school environment on the chemistry learning outcomes of students at MA NW Narmada. Utilizing a quantitative approach, the study targeted a population of 105 class XII students, with a sample of 50 students selected through random sampling using the Slovin formula. Data collection instruments included questionnaires, observations, interviews, and documentation. The findings reveal that the Islamic boarding school environment significantly influences students' chemistry learning outcomes, as evidenced by an f-table value of 10.59 > 4.05 and a significance value of 0.002 (< 0.05). Additionally, the study highlights that environmental indicators at the boarding school are categorized as very good for the social environment, good for the non-social environment, and good for student activities. The boarding school environment contributes an 18% influence on chemistry learning outcomes, distributed across social environment indicators (6.74%), non-social environment (5.52%), and student activities (5.74%).